2017
DOI: 10.1002/lary.26628
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol deficiency is a risk factor for idiopathic benign paroxysmal positional vertigo in postmenopausal female patients

Abstract: NA. Laryngoscope, 128:948-953, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 32 publications
2
23
0
2
Order By: Relevance
“…Previous studies have also suggested that women had a higher incidence of BPPV than in men, especially in the elderly women (4). This relationship may be related to estrogen deficiency in postmenopausal women, as estrogen may promote the development of osteoporosis and even BPPV (18). In addition, women BPPV patients have a higher risk of recurrence than men (9,31).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies have also suggested that women had a higher incidence of BPPV than in men, especially in the elderly women (4). This relationship may be related to estrogen deficiency in postmenopausal women, as estrogen may promote the development of osteoporosis and even BPPV (18). In addition, women BPPV patients have a higher risk of recurrence than men (9,31).…”
Section: Discussionmentioning
confidence: 97%
“…However, the underlying causes of BPPV remain unclear. In recent decades, many studies have investigated risk factors for the occurrence of BPPV, including female gender, serum vitamin D deficiency, osteoporosis, vascular risk factors, head trauma, and other potential risk factors (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). However, there are some controversies among these studies.…”
Section: Introductionmentioning
confidence: 99%
“…Similar findings were reported by Coksuer et al, the vertigo symptom gone after took hormone therapy (Coksuer et al, 2011 ). Furthermore, Yang et al conducted an animal study and the result showed the bilateral ovariectomy rat accepted female sex hormone replacement therapy were reversed the decrease of otoconin 90 levels (Yang et al, 2017 ). Otoconin 90 acts as main protein to maintain the normal morphology and growth of otoconia (Petko et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…Otoconia had loose morphology and were occasionally displaced into the semicircular canals in otoconin 90-null mice ( 25 ). Otoconin 90 expression levels were decreased in bilateral ovariectomy rats, while estrogen replacement reversed the decrease of otoconin 90 levels ( 26 ). Furthermore, bilaterally ovariectomised mice have significant balance-related behavioral deficits and that estrogen deficiency compromises otoconia maintenance and anchoring by reducing the expression of the otoconial component and anchoring proteins ( 27 ).…”
Section: Discussionmentioning
confidence: 99%